INFLUENCE OF VARIOUS SUBSTRATES ON PRODUCTIVITY AND ECONOMICAL EFFICIENCY OF CULTIVATION OF TOMATOES BY THE METHOD OF LOW-VOLUME HYDROPONICS - Kudiyarov R. I.; Dyamurshayeva E. B.; Sauytbayeva G. Z.; Dyamurshayeva G. E.; Tuleubayev Zhaxybay; Ziyaeva Gulnar (Scientific Journal of Pedagogy and Economics, 2021)
Currently, low-volume hydroponics is the most intensive system for vegetable plant cultivation in a greenhouse, the effective use of which largely depends on the selection of a substrate. The wide variety of substrates used for this technology suggests that when cultivating tomatoes in different regions, substrates from local raw materials can be used, making it possible to preserve all the positive properties of low-volume hydroponics and to get a high yield of tomatoes. This paper presents the results of a study on cultivating Lilos F1 tomatoes hybrid using substrates of peat (control option) and sawdust (SD) and rice husk (RH) in various ratios (SD 100%; RH 100%; SD: RH 50:50; SD: RH 75:25 and SD: RH 25:75). It was found that the highest tomato yield was received when growing tomatoes using a peat substrate (25.54 kg/m2 ) and in ratios SD: RH 75:25 and SD: RH 50:50 (27.70 and 24.57 kg/m2 ). The calculation of the economical efficiency of tomato cultivation showed that the level of production profitability was determined not so much by the yield as by the cost of the substrate, therefore the most effective was the use of composite substrates SD: RH 75:25 and SD: RH 50:50, which ensured the production profitability of 14.7% and 14.0%. The obtained results confirmed the expediency of using substrates from sawdust and rice husk to increase the efficiency of low-volume cultivation of tomatoes in regional conditions. It has been established that the use of substrates based on sawdust and rice husk for low-volume cultivation allows preserving all the positive properties of the technology and to get a rich yield of high-quality tomato fruits. The cost-effectiveness analysis of low-volume tomato cultivation using various substrates showed that the level of production profitability was influenced not so much by the yield as by the cost of the substrate. Since the region lacks natural reserves of organic substrates, when peat is used as a substrate, it has to be purchased from the CIS countries, which significantly affects the cost of production. The use of waste products from processing industries such as sawdust and rice husk as substrates, on the contrary, allows you to reduce this cost item in the cost of production and thereby increase the production profitability. The ground for doing research: Source of funding - grant of the Ministry of Education and Science of the Republic of Kazakhstan AP08956053 «Improving the production efficiency of greenhouse production in the Aral Sea region through the introduction of adapted innovative technology for low-volume tomato cultivation».